Examining the Influence of Interactive Artificial Intelligence Platforms on Individuals’ Daily Decision-Making - Alsaigh, Mustafa Othman; Saeed, Mustafa Gh. (PROSPECTIVE RESEARCHES, 2025)
This study aims to investigate the impact of interactive artificial intelligence platforms on the quality of daily decisions among individuals, focusing on the role of trust in these platforms as a mediating variable. The study used the descriptive-analytical approach, and data were collected from a sample of (100) university students from various disciplines. The study relied on a questionnaire that included three main axes: level of use, trust in the platform, and quality of daily decisions. The results of the statistical analysis revealed a high level of use of interactive platforms among sample members, and a strong, statistically significant relationship between use and trust, and between trust and decision quality. The results also showed that the impact of platforms does not vary based on demographic characteristics, reinforcing the notion of a comprehensive impact. The study concluded that interactive AI platforms are an effective tool in supporting individuals' daily decisions, provided they are used consciously and in a balanced manner. It recommended enhancing users' digital awareness and incorporating educational content on AI into university programs.